The Impact of Market Turbulence on Information Technology Governance and Organizational Agility - Yulia Dwi Wahyuni; Mustika Ramadhani; Hadi Supratikta (Indonesian Development of Economics and Administration Journal, 2024)
We employed a unique strategy to capture the relationship between IT governance and organizational agility: we added the dynamic capabilities view to the resource-based perspective. The relationship between IT governance and organizational agility is entirely mediated by IT and innovation capabilities, according to our analysis of senior managers' responses. They show how, in very unstable markets, IT governance and IT capability have a major impact on organizational agility, while in less turbulent markets, innovation capability has a major impact on organizational agility.